Value Relevance dari Informasi Akuntansi Sebelum dan Sesudah IFRS pada Perusahaan Sektor Property, Real Estate dan Konstruksi Bangunan - Listiyani Chandra; Juniarti Juniarti Juniarti (Business Accounting Review, 2018)
The application of IFRS as the main standard for the preparation of financial statements has been required in various countries around the world. Harmonization of international accounting standards brings various changes to performance and accounting information of the company. Therefore, companies need to pay attention to the benefits and usefulness of mandatory application of IFRS standards. This study intended to know the impact of IFRS implementation on the value relevance of accounting information. In addition, this study also intended to know the affect of accounting information on investor response as reflected by stock price movements.                   Data processing method was done by comparing pre and post IFRS by using descriptive statistical analysis, while data analysis method by using panel data regression analysis with STATA statistical software and hypothesis test was derived from financial report data obtained from yahoo finance company. The result of the study found that the application of IFRS in the property, real estate, and building sectors significantly influenced the increase of value relevance of accounting information in the form of EPS and BVPS.